DNA methylation profiles in cancer diagnosis and therapeutics - Pan, Yunbao; Liu, Guohong; Zhou, Fuling; Su, Bojin; Li, Yirong (Clinical and experimental medicine, 2018)
Cancer initiation and proliferation is regulated by both epigenetic and genetic events with epigenetic modifications being increasingly identified as important targets for cancer research. DNA methylation catalyzed by DNA methyltransferases (DNMTs) is one of the essential epigenetic mechanisms that control cell proliferation, apoptosis, differentiation, cell cycle, and transformation in eukaryotes. Recent progress in epigenetics revealed a deeper understanding of the mechanisms of tumorigenesis and provided biomarkers for early detection, diagnosis, and prognosis in cancer patients. Although DNA methylation biomarker possesses potential contributing to precision medicine, there are still limitations to be overcome before it reaches clinical setting. Hence, the current status of DNA methylation biomarkers was reviewed and the future use in clinic was also predicted.